Effect of Li nonstoichiometry and TiO2 addition on the microwave dielectric properties of Li3PO4 ceramics. Issue 14 (15th July 2022) - Gu, Huidong; Feng, Chang; Zhu, Hai-ou; Zhu, Haikui; Ding, Xifeng; Wang, Lixi; Zhou, Guohui; Wang, Meng; Ta, Shiwo; Zhang, Qitu
Abstract: Li3 PO4 ceramic is a promising microwave ceramic material with low dielectric constant. The effect of Li nonstoichiometry on phase compositions, microstructures, and microwave dielectric characteristics of Li3 PO4 ceramics, on the other hand, has been examined infrequently. Therefore, in the first part of this study, the stoichiometry and Li nonstoichiometry compositions based on Li3+x PO4 (x = 0, 0.03, 0.06, 0.09, 0.12 and 0.15) were prepared by conventional solid-phase method. The results show that a few nonstoichiometric lithium ions enter the lattice of Li3+x PO4 . Compared with the chemical content of Li3 PO4, the sintering characteristics, relative dielectric constants and quality factors of Li3+x PO4 ceramics can be improved by slightly excessive Li ions, while the properties of Li3 PO4 ceramics can be deteriorated by excessive Li ions. Li3.12 PO4 ceramics sintered at 975 °C for 2 h have good dielectric properties ( ε r  = 5.89, Q×f  = 44, 000 GHz, τ f  = −206 ppm/ ° C). In order to improve its large negative temperature coefficient of resonant frequency, in the following study, rutile nano TiO2 particles were added as τ f compensator. Adding TiO2 powders not only effectively improve the temperature stabilities of the multiphase ceramics, but also make the grain growth more uniform. With the increase of TiO2 content from 0.40 to 0.60, τ f increases from −73.5 ppm/ ° C to +42.3 ppm/ ° C. The best dielectric property of 0.45Li3.12 PO4 -0.55TiO2 composite ceramic is ε r  = 13.29, Q×f  = 40, 700 GHz, τ f  = +8.8 ppm/ ° C.